ANALISIS POTENSI WISATA MENGGUNAKAN INFORMASI GEOGRAFIS DAN STRATEGI PENGEMBANGAN PARIWISATA BERKELANJUTAN BERBASIS MASYARAKAT DI DESA SUMBERAGUNG, GROBOGAN, JAWA TENGAH - Bagasta, Adifa Risa; Iswara , Cahya; Lasally , Adesty (Jurnal Kepariwisataan Indonesia: Jurnal Penelitian dan Pengembangan Kepariwisataan Indonesia, 2021)
community-based sustainable tourism. Geographical information is needed to determine the distribution of tourism potential and to do an inventory of tourism potentials and attractions in Sumberagung Village. The research method used is a qualitative method with descriptive analysis to identify the tourism potential of Sumberagung Village and community-based sustainable tourism development. The research data is the coordinates of the potential and tourist objects, the results of interviews and photos of potential and tourist objects. The result of the research is that Sumberagung Village has natural resources that can be developed into tourist objects and can attract tourists. The management of tourism in Sumberagung Village is not optimal because there is no full community involvement in developing and managing the tourism potential of Sumberagung Village. Recommendations are given to provide references in the management and development of tourism in Sumberagung Village, mainly community-based development